Efficacy of T Regulatory Cells, Th17 Cells and the Associated Markers in Monitoring Tuberculosis Treatment Response - Agrawal, Sonali; Parkash, Om; Palaniappan, Alangudi Natarajan; Bhatia, Ashok Kumar; Kumar, Santosh; Chauhan, Devendra Singh; Madhan Kumar, M. (Frontiers in Immunology, 2018)
Treatment monitoring is an essential aspect for tuberculosis (TB) disease management. Sputum smear microscopy is the only available tool for monitoring, but it suffers from demerits. Therefore, we sought to evaluate markers and cellular subsets of T regulatory cells (Treg) and Th17 cells in pulmonary TB patients (PTB) for TB treatment monitoring. Peripheral blood mononuclear cells (PBMCs) were stimulated in vitro (with PPD) overnight which was followed by a polychromatic flow cytometry approach to study Treg and Th17 markers and cellular subsets in PTB (n =12) undergoing anti-tuberculous treatment (ATT). The baseline levels of these markers and cellular subsets were evaluated in normal healthy subjects (NHS). We observed a significant decline in the expression of CD25 (p<0.01) marker and percentage of T cell subsets like CD4+CD25+ (p<0.001) and CD4+CD25+CD39+ (p<0.05) at the end of intensive phase (IP) as well as in the continuation phase (CP) of ATT. A decline in CD25 marker expression and percentage of CD4+CD25+ T cell subset showed a positive correlation to sputum conversion both in high as well as low sputum positive PTB. In 8 PTB with cavitary lesions, only CD4+CD25+FoxP3 Treg subset manifested a significant decline at the end of CP. Thus, results of this study show that CD25 marker and CD4+CD25+ T cells can serve as better markers for monitoring TB treatment efficacy. The Treg subset CD4+CD25+FoxP3 may be useful for prediction of favourable response in PTB with extensive lung lesions. However these findings have to be evaluated in a larger patient cohort.